Analisis Pengaruh Harga, Viral Marketing dan Kelompok Acuan Terhadap Pengambilan Keputusan Pembelian Mie Gacoan - Aries Binedikta; Terimaniati Telaumbanua; Ketetapan Waruwu; Rido Krisman Gea; Agustini Tanjung (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
ABSTRACT In modern times, there have been many advancements in the business world. Competition is extremely fierce, and all manufacturers are developing their businesses to win the competition. The purpose of the study was to analyze the influence of price and service quality on consumers' purchasing decisions in Mie Gacoan Lippo Cikarang branch. This study adopts a quantitative method using primary data from a questionnaire distributed to consumers at the Mie Gacoan Lippo Cikarang branch. The sample used included 105 respondents based on the purposive sampling method. Data analysis methods, namely descriptive statistics, coefficient of determination, correlation coefficient, significant F test, significant t test. The results showed that price and service quality perceptions simultaneously influenced purchase decisions. The findings suggest that Mie Gacoan will strive to increase the purchasing power of consumers through lower prices and increased promotions of the products it offers. The results of this study can be used as a references by developing variables to study and further developing the study by adding populations and samples. Keywords: price, service quality, purchase decision